IMPROVING THE ABILITY TO WRITE DESCRIPTION TEXT USING TOPIC CARD MEDIA FOR CLASS VII STUDENTS AT SMP NEGERI 6 PALU - Ni Gst Ayu Pt Sintya Dewi; Ida Nur’aeni; Wayan Sutarmi (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to improve the ability to write descriptive text using topic card learning media for class VII Andalan SMP Negeri 6 Palu students. This research was carried out in two cycles involving an assessment of the results of observing images, the suitability of the text structure and the results of creative use of vocabulary. Topic card media helps students organize ideas and information in a structured manner so that it helps them write good descriptive texts. This type of research is Classroom Action Research (CAR) using the Kemmis and McTaggart model which consists of four stages of planning, implementation, observation and reflection. The data obtained in this research was through written tests, observations and interviews. The research results show that the use of topic cards can improve students' abilities, which is aimed at increasing the average from cycle I to cycle II. Topic cards can also increase students' interest and desire to learn to write. This research makes a significant contribution to the development of Indonesian language learning. This research recommends the use of topic card media as an innovative learning alternative.